Governance and communities of PMOs - Aubry, Monique (Project Management Institute, 2012)
Cover -- Title Page -- Copyright Page -- Table of Contents -- List of Figures -- List of Tables -- Executive Summary -- Acknowledgments -- 1. Introduction -- 1.1. Context of this Research -- 1.2. This Research within the PMO Research Program at UQAM -- 2. Literature Review and Conceptual Framework -- 2.1. How do Project Management Offices Support the Circulation of Knowledge? -- 2.2. Multiple PMOs: Islands, Networks, or Communities? -- 2.2.1. Usefulness of the Metaphor of Island -- 2.2.2. Networks -- 2.2.3. Organizational Learning: A Community of Practice Approach -- 2.3. Managing Multiple PMOs: The Governance Challenge -- 2.3.1. Governance of Projects -- 2.3.2. Governance of Multi-PMO Structures -- 2.4. Conceptualization of Communities of PMOs -- 2.4.1. Definition of Community of PMOs -- 2.4.2. Social World of Community of PMOs -- 2.4.3. Governance -- 2.4.4. Structure of Relationships between PMOs -- 2.4.5. Linking Social World and Governance to the Structure of Relationships -- 3. Research Design and Methodology -- 3.1. Underlying Philosophy -- 3.2. Research Design -- 3.3. Case Sampling -- 3.4. The Qualitative Study -- 3.4.1. Data Collection Strategy -- 3.4.2. Interviewee Sampling -- 3.4.3. Interview Questions -- 3.4.4. Validity and Reliability of the Interview Data -- 3.4.5. Interview Analysis -- 3.5. The Quantitative Study -- 3.5.1. Social Network Analysis -- 3.5.2. Data Collection -- 3.5.3. Questionnaire Development -- 3.5.4. Validity and Reliability of the Data -- 4. Descriptions of Case Studies -- 4.1. Case Study 1: Telecommunications Provider -- 4.1.1. Context -- 4.1.2. Project Governance -- 4.1.3. PMOs' Formal Structure -- 4.1.4. Governance of Multiple PMOs -- 4.1.5. Relationships between PMOs -- 4.1.6. Learning Mechanisms -- 4.2. Case Study 2: National Health Care Organization -- 4.2.1. Context -- 4.2.2. Project Governance